Digital finance and financial literacy: Evidence from Chinese households - Yang, Junhong; Wu, Yu; Huang, Bihong (Journal of Banking & Finance, 2023)
We measure financial literacy and study its impact on household use of digital finance using the 2015 and 2017 China Household Finance Survey. We find that financial literacy significantly boosts the use of digital finance, including mobile payments, online borrowing, and online financial products. This effect is more pronounced for online borrowing and online financial products than for mobile payments. This result suggests that the impact of financial literacy increases with the complexity of digital finance. Furthermore, financial literacy plays a more important role in promoting the use of digital financial services among disadvantaged groups, such as families with low income and wealth, the elderly, and residents in rural areas, compared with their counterparts.